Age rather than diabetes duration predicts the severity of sensory neuropathy in type 2 diabetes mellitus - Kiss, Áron T.; Kézdi, Árpád; Békeffy, Magdolna; Koós, Csaba G; Körei, Anna E.; Menyhárt, Adrienn; Balogh, Dóra M.; Kempler, Péter; Tabák, Ádám Gy.; Horváth, Viktor J. (Frontiers in Endocrinology, 2026)
IntroductionIn patients with type 2 diabetes, factors beyond hyperglycemia may contribute to the development of sensory neuropathy. This study aimed to determine whether diabetes duration was the strongest predictor of prevalent sensory neuropathy and to compare the diagnostic performance of commonly used clinical screening methods.Materials and methodsA total of 711 patients with type 2 diabetes from the Budapest metropolitan area were assessed between 2016 and 2022 using routine sensory neuropathy screening tests (128-Hz tuning fork and 10-g monofilament). A brief standardized questionnaire was also administered to support neuropathy detection. Independent predictors of sensory neuropathy were identified using binary logistic regression models and interrater agreement between diagnostic methods was assessed with Cohen’s kappa.ResultsAgreement between diagnostic methods was only moderate (Cohen’s kappa: 0.3–0.4). In the final adjusted models, age emerged as the only independent predictor of neuropathy detected by tuning fork testing (OR 1.04; 95% CI 1.02–1.06), whereas for the monofilament test, self-reported neuropathic symptoms remained independently associated. Consistent with this, positive responses to standardized symptom questions correlated with both diagnostic tests, supporting their clinical validity.ConclusionThe overlap between routinely applied clinical methods for detecting sensory neuropathy is limited. Our findings suggest that, in an aging population with type 2 diabetes, peripheral nerve damage identified by standard screening tools is more strongly associated with age than with diabetes duration when assessed by commonly used bedside screening tools. Prospective studies are warranted to better differentiate diabetic neuropathy from age-related nerve dysfunction.